Answer:
x=6.566084 or x=−1.066084
Explanation:
Let's solve your equation step-by-step.
−4
x
−1=
7
2
−x+
3
x
+1
−4
x
+−1=
7
2
+−x+
3
x
+1
Multiply all terms by x and cancel:
−4+−1x=
7x
2
+(−x)(x)+3+1x
−x−4=−x2+
9
2
x+3(Simplify both sides of the equation)
−x−4−(−x2+
9
2
x+3)=−x2+
9
2
x+3−(−x2+
9
2
x+3)(Subtract -x^2+9/2x+3 from both sides)
x2+
−11
2
x−7=0
For this equation: a=1, b=-5.5, c=-7
1x2+−5.5x+−7=0
x=
−b±√b2−4ac
2a
(Use quadratic formula with a=1, b=-5.5, c=-7)
x=
−(−5.5)±√(−5.5)2−4(1)(−7)
2(1)
x=
5.5±√58.25
2
x=6.566084380618436,−1.0660843806184368
Check answers. (Plug them in to make sure they work.)
x=6.566084(Works in original equation)
x=−1.066084(Works in original equation)
Answer:
x=6.566084 or x=−1.066084